SEGMENTATION OF MEDICAL ULTRASONIC IMAGES BASED ON FUZZY CLUSTERING - Pisa, D. M.; Stepanenko, A. A. (Radio Electronics, Computer Science, Control, 2024)
A new approach to increasing efficiency of visual analysis ultrasonic medical pulse-echo image is considered. Results experimental investigation information possibilities of the new method are presented.